Resolution of Osseous Sarcoidosis with Methotrexate - Christopher Kanner; Bonita Libman; Morgan Merchand; Diego Lemos (Case Reports in Rheumatology)
Though a relatively uncommon manifestation of sarcoidosis, some clinicians are tasked with managing osseous involvement of disease, and the optimal treatment approach in this setting is not well established. Previous studies have shown variable efficacy for osseous sarcoidosis utilizing multiple agents alone or in combination, often using imaging follow-up in conjunction with clinical assessment to evaluate response to treatment. We present a case of widespread skeletal involvement of sarcoidosis without evidence of concurrent pulmonary disease demonstrating marked clinical improvement and near-complete resolution of imaging abnormalities on magnetic resonance imaging (MRI) following the use of methotrexate as the primary pharmacologic agent.